Giant Cutaneous Horn (Cornu Cutaneum) Developing from a Hypertrophic Burn Scar. (February 2022) - Cosansu, Nur Cihan; Cetiner, Tuba; Yuksekal, Gülcan
Abstract : ABSTRACT: A cornu cutaneum (CC) is a rare lesion. This case report describes a 63-year-old woman with a giant CC lesion on her right hip arising from a hypertrophic burn scar at its base. To the authors' knowledge, this is the first case described in the literature of a CC that developed from a burn scar.